(untitled) (Enlace UIC: Revista de Investigación de la División de Posgrados de la Universidad Intercontinental, 2021)
Innovation is something desirable in the business world and it is a concept or phenomenon that has been prolific in the literature on the matter. However, there is little evidence regarding the genesis of the phenomenon, since in most cases it is conceived as something natural or as the result of a learning process. This article tries to reflect on the factors that can be considered as sources or triggers of the activity: the need, experience and knowledge to, based on divergent and convergent thinking styles, highlight the role of administrative management as articulating axis of innovative activity in the business field.